The Effect of The Characteristics of The Internal Governance Mechanisms on The Growth Opportunities: The Tunisian Evidence - Raida Chakroun (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- Do the characteristics of the board of directors and the characteristics of audit committee influence Tunisian companies' growth opportunities? Motivation- Attract the attention of policy makers to design appropriate governance mechanisms for emerging countries in general and specifically for Tunisia. More specifically, we hope to gain a better understanding of the function of audit committees and board of directors in enhancing firm growth opportunities. Idea- This paper investigated of the impact of the internal governance mechanisms characteristics such as board of directors and audit committee on Tunisian companies' growth opportunities. Data- We based on a sample of 38 non-financial firms listed on Tunis Stock Exchange observed on the period 2013-2019. Tools- We used the multivariate regression method on panel data. Findings- We found that the of board of directors 'size and the frequency of the audit committee meetings impact negatively the firm's growth opportunities. Contribution- The findings of our study may be useful for the shareholders to make appropriate choices about the composition of the board of directors and the audit committee to enhance growth opportunities. The shareholders should not encourage the institution of larges boards and frequent meetings of the audit committees.
Keywords: G3; D1; 650; Internal Governance Mechanisms; Board of Directors; Audit Committee; Growth opportunities